A study into cyber risks with respect to smart port development - Yap, Paige Charlotte Tze Shuen (Nanyang Technological University, 2023)
In today’s interconnected world, the rapid advancement of technology has ushered in a new era of “smart” infrastructure, transforming traditional ports into intelligent and interlinked ecosystems. However, with this digital transformation comes the heightened risk of cyber threats and vulnerabilities. This research paper aims to delve into the multifaceted realm of cyber risks surrounding smart port development, hoping to uncover the hidden perils which lie within this promising yet uncharted domain. Drawing upon extensive research and analysis, this study examines the intricate interplay between technological innovation and cyber vulnerabilities in the context of smart ports. It explores the evolving threat landscape, where adversaries harness the power of cyberspace to exploit vulnerabilities in port systems, disrupting critical operations, compromising data integrity, and endangering the very foundation of global trade. Ultimately, this study serves as a wake-up call to the port industry, policymakers, and cybersecurity practitioners. By comprehensively understanding these threats, stakeholders can then forge effective strategies to mitigate and manage cyber risks in the pursuit of resilient and secure smart port ecosystems. The accuracy and reliability of the information presented in this paper have been ensured by conducting multiple questionnaires and focused studies, which validate and confirm the findings.